Surveying the exposure level of intimidation (mobbing) behaviours of the football referees - Hacicafero?lu, Serkan; Gündo?du, Cemal (My University, 2014)
The purpose of this study is to determine the level of psychological mobbing behaviors that the football referees within Turkey Football Federation are exposed to. The sampling of the study conducted by using a screening model is consisted of 374 referees, actively working in various leagues. The research data were collected by a Mobbing Scale for Football Referees. In the study were used descriptive statistics, Tukey test, t-test and one-way analysis of variance (ANOVA). As a result of the survey, it was found out that women compared to men, married referees to single referees, the referees with postgraduate education compared to the other educational groups, the referees of 23-27 age group compared to the other age groups, the referees of 1 to 4 tenure compared to other tenure groups, were more exposed to mobbing behaviors. It was determined that there was a statistically significant difference between the mobbing behaviors according to the variable of gender, marital status, education, ages of the referees, and that there was no any significant difference according to the tenure variable. In addition, it was concluded that the participated referees were exposed to various mobbing behaviors at lower medium levels in total. © JPES.
Keywords: Football referees; Mobbing; Psychological intimidation; Referees